Imaging Patterns in Depressive Disorder: A Comprehensive Magnetic Resonance Imaging Assessment of Brain Anatomy - Nadhrati Surura, Hedya; Yuslila, Ewi; Amris, Fazil; Al Bukhari, Al Bukhari; Fitria, Syukria (GALENICAL : Jurnal Kedokteran dan Kesehatan Mahasiswa Malikussaleh, 2025)
This literature examines the significant role of magnetic resonance imaging (MRI) in the diagnosis and evaluation of the anatomical features of the brain in patients with depressive disorders. A comprehensive understanding of psychiatric mechanisms through imaging techniques facilitates the development of more effective strategies for managing individuals with depression. Reference sources come from international journals obtained systematically from reputable databases; PubMed, Science Direct and Scopus with a range of publication years from 2020 to 2024. The keywords used in this literature searching process are "Hippocampus" "Amygdala", "Prefrontal Cortex", "Cyngulate Cortex", “Nucleus Accumbens”, “Brain”, “Imaging”, and "MRI". A Comprehensive literature search using the Bollean concept resulted in 1,827 articles which were then selected based on the inclusion and exclusion criteria of 4 articles. Articles were selected based on their relevance with a focus on Magnetic Resonance Imaging (MRI) techniques in Depressive Disorder cases. This comprehensive review summarizes MRI findings in key brain regions in depressive disorder, including the hippocampus, amygdala, prefrontal cortex, cingulate cortex, and nucleus accumbens, highlighting both structural and functional abnormalities. The results reveal volumetric reductions and altered functional connectivity, particularly in mood-regulating areas, which are linked to cognitive deficits and emotional dysregulation in individuals with depression. Understanding these neurobiological changes is crucial for developing targeted therapeutic interventions, offering potential pathways for more effective, personalized treatments for depressive disorders.